THE TREATMENT OF THE ORAL MUCOSA IN CHRONIC RECCURENT APHTHOUS STOMATITIS (International journal of artificial intelligence, 2026)
Chronic recurrent aphthous stomatitis is an inflammatory disease of the SOPR, characterized by the appearance of aphthous lesions, a long course with periodic relapses and is often accompanied by diseases of the gastrointestinal tract. Chronic cholecystitis is an inflammatory disease of the gallbladder wall. It develops due to the formation of gallstones in the gallbladder, which leads to stagnation of bile. Periodically occurring and passing inflammations lead to changes in the wall of the gallbladder with the development of chronic calculous cholecystitis in it. Along with the general clinical signs of chronic calculous cholecystitis, changes in the oral mucosa develop.